2021
DOI: 10.1186/s12951-020-00757-5
|View full text |Cite
|
Sign up to set email alerts
|

Neural progenitor cell-derived nanovesicles promote hair follicle growth via miR-100

Abstract: Background Accumulating evidence shows that mesenchymal stem cell-derived extracellular vesicles (EVs) hold great promise to promote hair growth. However, large-scale production of EVs is still a challenge. Recently, exosome-mimetic nanovesicles (NV) prepared by extruding cells have emerged as an alternative strategy for clinical-scale production. Here, ReNcell VM (ReN) cells, a neural progenitor cell line was serially extruded to produce NV. Results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…Furthermore, miR-100 inhibition verified its key role in ReN-NV-induced β-catenin signaling activation. This study provides the potential for large-scale production of NVs for hair growth therapies ( Cao et al, 2021 ).…”
Section: Cell-derived Nanovesicles and Their Action Of Mechanism For ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, miR-100 inhibition verified its key role in ReN-NV-induced β-catenin signaling activation. This study provides the potential for large-scale production of NVs for hair growth therapies ( Cao et al, 2021 ).…”
Section: Cell-derived Nanovesicles and Their Action Of Mechanism For ...mentioning
confidence: 99%
“…In addition, fibroblast-derived EVs induced ORSC differentiation by increasing the transcriptional expression of keratins ( Rajendran et al, 2021b ), whereas activated fibroblast-derived EVs regulated the Norrin-encoding genes of DPCs ( Riche et al, 2019 ). Another study showed that human neural progenitor cell - derived EVs containing miR-100-5p increased the levels of β-catenin, C-myc, and Cyclin D1 in DPCs and these effects were abolished when miR-the DPCs were treated with miR-100-5p inhibitors ( Cao et al, 2021 ). Finally, mouse ADSC-derived EVs were shown to carry low levels of miR-22-5p and miR-22-3p; use of inhibitors against miR-22 diminished the hair inductive ability ( Li et al, 2022 ).…”
Section: The Mechanisms Of Action Of Extracellular Vesicles Cargoes I...mentioning
confidence: 99%
See 1 more Smart Citation
“…CTNB plays an important role in cell cycle progression, cell proliferation, and gene regulation of Cyclind1 and c-Myc , as well as Ctnb . Upon Ctnb activation, it accumulates cytoplasm and translocates into the nucleus [ 34 ], and then transcriptionally regulates various events, such as the maintenance of the HF anagen phase [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al injected NV extruded from ReNcell VM (ReN) cells, a neural progenitor cell line, in a mouse model. 92 The results showed that the NV promoted the proliferation of DPC and accelerated HF cycling transition by miR-100 to activate the Wnt/β-catenin signaling pathway. 92 This study therefore highlighted a possible method for the large-scale production of EVs in future.…”
Section: Promoting Hair Growthmentioning
confidence: 97%